2015
DOI: 10.1155/2015/718701
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment, Depression, and Cooccurrence of Both among the Elderly in Panama: Differential Associations with Multimorbidity and Functional Limitations

Abstract: Cognitive impairment and depression are common mental health problems among the elderly, although few studies have examined their cooccurrence in older adults in Latin America. The purpose of this study was to examine cognitive impairment, depression, and cooccurrence of the two conditions and associated factors in a sample of older adults in Panama. This study included 304 community-dwelling elderly (≥65 years) individuals. Participants underwent a clinical interview and assessments of cognitive function by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
(47 reference statements)
0
17
1
4
Order By: Relevance
“…The data from the China Health and Retirement Longitudinal Study (CHARLS) in 2013 [ 24 ] found that the overall prevalence of disability among adults aged 80 years or more was 21.9%. The prevalence of disability in our study is higher than other recent studies [ 25 , 26 ], which may result from the following considerations. Firstly, previous studies assessed disability according to ADL and IADL [ 9 , 27 ], without considering the impact of impairment of sensory perception, social participation and mental status on compromising independent living status.…”
Section: Discussioncontrasting
confidence: 71%
“…The data from the China Health and Retirement Longitudinal Study (CHARLS) in 2013 [ 24 ] found that the overall prevalence of disability among adults aged 80 years or more was 21.9%. The prevalence of disability in our study is higher than other recent studies [ 25 , 26 ], which may result from the following considerations. Firstly, previous studies assessed disability according to ADL and IADL [ 9 , 27 ], without considering the impact of impairment of sensory perception, social participation and mental status on compromising independent living status.…”
Section: Discussioncontrasting
confidence: 71%
“…There is a mutually promoting function between loneliness and depressive symptoms10. They exhibit deleterious effects on mental wellbeing as well as on physical health.…”
mentioning
confidence: 99%
“…Females were more prone to experience severe depression and suffering no depression, while males suffered more mild depression than females, the same percent of both genders experienced moderate depression, (P-value=0.008). No association between depression and gender was shown in Indian study (Villarreal, et al 2015). Education was a factor that affected the degrees of depression (P-value=0.001), the participants with a university and above education experienced severe depression more than those of less education, while more participants with education less than university suffered no depression.…”
Section: Discussion:-mentioning
confidence: 74%